The Determinant Factors of Auditor Switch (Empirical studies to Companies listed on Indonesian Stock Exchange) - Sri Yunawati; Zulkarnain Zulkarnain (International Journal on Advanced Science, Education, and Religion, 2019)
In Indonesian, regulation about change auditor subsit on regulation of finance minister of Republic Indonesia Number 17/PMK.01/2008 article 3rd, requires the audit public services for financial reports of an entity by public accountant office branch maximum for 6 (six) book years in a row and a auditor maximum 3 (three) book years in a row. This study did in manufacturing companies listed in Indonesian Stock Exchange (IDX’s) on 2018. The aim of this research is to find major determinants of auditor switch among companies listed onIndonesian Stock Exchange. The research used statistic wald test at level significancy is 5%, the presents that change of management, firm size, , Public Accountant Office Branch Size, and fees audit thatt there is no affect significant impact on the auditor switching in manufacturing companies who listed at Indonesian Stock Exchange (IDX’s)